DEVELOPMENT OF PLASMID-BASED FOR EXTERNAL CONTROL MATERIALS OF CYP2D6*10 (rs1065852) GENE PCR-BASED DETECTION - Malau, Jekmal; Zahra, Aliya Azkia; Kasasiah, Ahsanal; Rahmasari, Ratika; Raekiansyah, Muhareva; Rohmah, Siti; Meilani, Nanda Diva; Septi, Annisa Frastica; Zahro, Aurora Fatimatuz; Annajla, Fathina; Hermosaningtyas, Anastasia Aliesa; Hilmi, Indah Laily (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Reliable clinical diagnosis of Single Nucleotide Polymorphisms (SNPs) is necessary for personalizing tamoxifen medication according to CYP2D6*10 genetic variations. Our research aimed to create a recombinant plasmid for external control material with a molecular size of 3812 bp. The recombinant plasmid was achieved by cloning an 838 bp gene insert of CYP2D6*10 rs1065852 into a 2974 bp pJET1.2 plasmid into Escherichia coli DH10B and selection on ampicillin agar medium. Isolated E. coli recombinants provided the plasmid molecules for analysis. Bi-directional sequencing and Real-Time PCR confirmed the presence of wild-type and mutant rs1065852 DNA fragments in the plasmid, namely homozygote CC and TT. The conclusion is that we have successfully introduced a novel recombinant plasmid developed by cloning the SNP rs1065852, which carries the 100C>T mutation, using pJET 1.2/blunt system, which could significantly enhance the accuracy of clinical SNP diagnostics for personalized medicine in breast cancer treatment.